Description of Dating Experience In Adolescents: A Phenomenological Study - Devita, Chalsea; Nugrahaeni Widiasavitri, Putu (Green Publisher Indonesia, 2023)
Adolescence is a transition phase from childhood to adulthood with various physical, cognitive, and psychosocial adjustments. A romantic relationship or dating is a phenomenon that allows adolescents to explore their intimacy and sexuality. However, dating can also have numerous negative impacts on adolescents such as a higher risk of being infected by sexually transmitted diseases and unwanted pregnancy. This study aims to understand dating experiences in adolescents. The method used in this study is qualitative research with a phenomenological approach. Using individual analysis units, the participants in this study were five early to late adolescents from Bali aged 12-21 years who are currently dating. The data analysis process is conducted using Interpretative Phenomenological Analysis (IPA) technique contains five steps. Based on the analysis process, this study produced findings where there was interaction in adolescents before establishing a dating relationship, after deciding to have a relationship, adolescents would interpret the presence of their partner. In carrying out their relationship, teenagers have values that form the basis of the relationship. In addition, parents also have a large involvement in adolescent dating relationships. Intense togetherness in teenage dating relationships is considered to be an important thing, teenage dating can provide good or bad changes. Other findings discuss conflicts that occur in adolescents and how adolescents resolve them